Desenvolvimento, caracterização, avaliação da eficácia in vitro, in vivo e farmacocinética de nanopartículas de superfície modificada contendo quinina - Michels, Luana Roberta (2016)
The increase of Plasmodium falciparum resistance difficult the treatment of malaria, and the use of higher doses of the drug induce toxicity. The coating of nanoparticles have been studied with the purpose of improve the in vivo performance of drugs. The aim of this study was to develop, characterize and evaluate the efficacy in vitro, in vivo and pharmacokinetics of quinine (QN) loaded-nanoparticles with different surface characteristics: polysorbate 80 coated-nanocapsules; PEG coated-nanocapsules and nanocapsules prepared with Eudragit® RS 100. The suspensions were prepared by nanoprecipitation method and characterized according to the diameter, polydispersity, pH, zeta potential, content encapsulation rate and atomic force microscopy. The nanoparticles showed the best results on the characterization and in vitro efficacy were chosen for evaluating the in vivo efficacy and pharmacokinetics, using Wistar rats and mice infected with P. berghei. The nanocapsules showed the best results in the physical-chemical characterization, with appropriate diameter, monodisperse population, zeta potential distant from zero, the higher rate of encapsulation and intra-erythrocyte penetration. There was a significant increase in t1/2 of all nanocapsules evaluated in comparison to free QN. On the efficacy in vivo, cationic nanocapsules increased the survival rate compared to saline and to the free QN, demonstrating that the drug incorporated in the suspension with cationic characteristics can alter the efficacy of QN presenting as a potential alternative for the treatment of malaria.